Is there any difference in Lactobacillus abundance between age groups during ovarian stimulation in fresh in vitro fertilization (IVF) cycles? - Haris Zukić; Devleta Balić; Džanan Osmanović (Medicinski glasnik, 2024)
Aim: To investigate an influence of age and body mass index (BMI) as determinants of infertility treatment success in vitro fertilization (IVF) procedures confirmed so far, on the amount of Lactobacillus spp. (LS) and Gardnerella vaginalis (GV) in the endometrium in fresh IVF cycles at the time of embryo transfer. Methods: This a prospective single-centre study included patients who underwent fresh embryo transfer (ET) in a private IVF Centre. A catheter tip for embryo transfer was used for collecting samples from the endometrial cavity. Real time polymerase chain reaction (RT PCR) was used to determine LS and GV quantity. Patients were divided into two age groups: <35 years and ?35 years. Normal BMI group included patients with 18.-24.9 kg/m 2 , and the in-creased BMI group patients with BMI ? 25kg/m 2 . Results: Tips for embryo transfer catheters were positive on LS in 55 (96.4%) patients. The median of quantification cycle of RT-PCR (Cq RT-PCR) for LS was 33, and 31 for the younger and older groups, respectively. Twenty-one (36.8%) patients tested positive for GV. The median of Cq RT-PCR for GV was 33 and 34 for the younger and older groups, respectively. There were 36 patients with normal and 18 with increased BMI. BMI showed no correlation with LS amount in the endometrial cavity. Conclusion: Aging affects the endome-trial microbiome resulting in an increase of Lactobacillus number, but not the number of GV.
Keywords: assisted reproduc-tive technologies; endometrium; hu-man reproduction; reproductive tract bacteria